Enhanced physical properties of stable lead-free oxide double perovskite Ba2TbBiO6 for photovoltaics: Effects of Sb doping - Samiron Kumar Saha; Mithun Khan; Zahid Hasan; Dayal Chandra Roy; Md Lokman Ali (AIP Advances, 2024)
The effect of Sb-doping in the Bi-based double perovskite Ba2TbBi1-xSbxO6(x = 0.0, 0.5) on providing a structural and electronic framework for understanding numerous physical aspects at an atomistic level. We study in detail the undoped and Sb-doped Ba2TbBiO6 double perovskite’s structural, elastic, mechanical, electronic, and thermodynamic properties for both cubic and monoclinic phases. Doping alters the spatial group structure and lattice constant of Ba2TbBi1−xSbxO6, causing a change in the Brillouin zone, which alters the band structure and bandgap value. The elastic constants confirmed the ductility of the solids and ensured mechanical stability in both phases. This study reveals that both phases of Ba2TbBi1−xSbxO6 are more mechanically stable, ductile, and machinable than Ba2TbBiO6. The Sb-doped monoclinic phase had greater anisotropy than the cubic phase, despite the fact that both phases were anisotropic. Vickers hardness shows that the monoclinic Ba2TbBi1−xSbxO6(x = 0.0, 0.5) phase is harder than the cubic Ba2TbBi1−xSbxO6(x = 0.0, 0.5) phases. The cubic and monoclinic phases of Ba2TbBi0.5Sb0.5O6 have Debye temperatures of 248.48 and 240.75 K, respectively. After doping, the cubic phase’s melting temperature (1529.21 K) grows higher than that of the monoclinic phase (1386.87 K). Doping can make a material more stable by lowering its thermal expansion coefficient. Both doped phases can be used as thermal barrier coatings (TBCs).